2019
DOI: 10.1063/1.5059370
|View full text |Cite
|
Sign up to set email alerts
|

Reducing deposition of encrustation in ureteric stents by changing the stent architecture: A microfluidic-based investigation

Abstract: Ureteric stents are clinically deployed to retain ureteral patency in the presence of an obstruction of the ureter lumen. Despite the fact that multiple stent designs have been researched in recent years, encrustation and biofilm-associated infections remain significant complications of ureteral stenting, potentially leading to the functional failure of the stent. It has been suggested that “inactive” side-holes of stents may act as anchoring sites for encrusting crystals, as they are associated with low wall … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 42 publications
3
32
1
Order By: Relevance
“…Staining with crystal violet did not show any detectable bacterial attachment in this device, including within inactive side-holes, where the average WSS is << 40 mPa. These findings appear to differ from the recent studies by Mosayyebi et al [20], which showed deposition of encrusting particles within inactive side-holes in a similar stent-on-a-chip device. It should, however, be noted that the amount of particle deposition and attachment over a surface (within a given fluidic domain) likely depends on both mass flow rate of the particle (i.e., mass of flowing particles per unit time), sedimentation rate, and the level of WSS over the surface.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Staining with crystal violet did not show any detectable bacterial attachment in this device, including within inactive side-holes, where the average WSS is << 40 mPa. These findings appear to differ from the recent studies by Mosayyebi et al [20], which showed deposition of encrusting particles within inactive side-holes in a similar stent-on-a-chip device. It should, however, be noted that the amount of particle deposition and attachment over a surface (within a given fluidic domain) likely depends on both mass flow rate of the particle (i.e., mass of flowing particles per unit time), sedimentation rate, and the level of WSS over the surface.…”
Section: Discussioncontrasting
confidence: 99%
“…As for the obstructed I SoC device (i.e., with an occlusion located 4.5 mm away from the proximal side-hole), CFD simulations showed very low levels of wall shear stress within the hydrodynamic cavity formed in proximity to the occlusion (WSS << 40 mPa). This region is also characterised by the presence of laminar eddies, as previously reported [20,22]. Moreover, simulations revealed that the presence of a ureteral occlusion diverted a greater amount of fluid flow through the proximal side-hole, resulting in increased WSS levels in this hole compared to the unobstructed case.…”
Section: Ureteral Obstructions Promote Bacterial Attachmentsupporting
confidence: 73%
See 3 more Smart Citations